Identifikasi Penerapan Biophilic Design pada Interior Rumah Sakit - Raden Roro Monica Synthia Permata Dewi; Yusita Kusumarini; Anik Rakhmawati (Intra, 2018)
Hospital is one of essential aspects in the scope of people’s health. Hospital design often makes patient feeling anxiety and uncomfortable because of the hospital’s atmosphere that seems gripping and creepy. The atmosphere of hospital design impacts patient’s psychology and their physical condition. Basically, human has a tendency to stay in touch with nature that could affects their psychology and physical condition positively which is called as biophilia. This led to the use of design approach called biophilic design. Biophilic design has 14 patterns that can be used to create designs that is related with nature. The application of biophilic design in the hospitals is believed to create a healing environment. However, to apply biophilic design to hospitals, we should consider the requirements that must be met for hospital building so as not to risk the patient aand not to support the disease spreading process in the hospital. This study was conducted with the aim to describe what kind of biophilic design pattern that can be applied in hospital interior. The type of research used is qualitative descriptive. The data analysis process resulted in 2 out of 14 biophilic design patterns are not applicable to hospital interiors they are Mystery, Risk & Peril.  12 patterns that can be applied are Visual connection with nature, Non-visual connection with nature, Non-rhytmic stimuli, Thermal and airflow variability, Dynamic and diffuse lighting, Connection with natural system, Biomorphic forms and patterns, Complexity and Order, Prospect and Refuge.